Transformasi Pecandu Penyandang HIV/AIDS Menjadi Konselor Adiksi: Sebuah Kajian Life History - Qori Faizun; Nurchayati Nurchayati (Universitas Negeri Surabaya, 2021)
Using Giddens structuration theory and Banduras concept of agency, this quasi-life-historical study deals with how an interplay between agency and social structure produced the transformation of a participant from a drug addict with HIV/AIDS into an addiction counselor. In response to the structural forces at work in her society, the subject exercised her agency in ways that led, as an unintended consequence, to her contracting HIV/AIDS. Drug abuse, too, was another of her self-defeating ways of tackling lifes trials, such as the excess of pocket money, dysfunctional family communications, and stifling parental disciplinary styles. Structural forces, taking the forms of rehabilitation facilities and family and community supports, played a key role in her success in kicking her drug habit and becoming an addiction counselor. The transformation, however, is best seen as the product of a favorable interplay between existing structural forces and the subjects constructive ways of enacting her agency.Keywords: Agency, structure, drug addict, HIV/AIDS, addiction counselor Abstrak: Menggunakan metode quasi-life history, riset kualitatif ini mengkaji transformasi subjek dari pecandu penyandang HIV/AIDS menjadi konselor adiksi. Merujuk pada teori strukturasi Giddens dan konsep agency dari Bandura, studi ini mencoba memahami bagaimana struktur dan agency berinteraksi dan menghasilkan transformasi tersebut. Menjadi penyandang HIV/AIDS adalah akibat yang tidak diniatkan (unintended consequence) dari cara subjek menjalankan agency-nya dalam menanggapi daya-daya struktural dalam masyarakat. Dalam menyikapi peraturan orang tua, ketidakharmonisan komunikasi keluarga dan berlebihnya uang saku, subjek justru mengonsumsi NAPZA. Di sisi lain, ada sejumlah daya struktural yang membantu subjek membebaskan diri dari adiksi dan menjadi konselor, seperti program rehabilitasi, dukungan masyarakat sekitar, dan membaiknya sikap keluarga. Alih-alih bekerja sendiri, daya-daya struktural tersebut bersinergi dengan perjuangan subjek. Studi ini menyimpulkan bahwa transformasi subjek dari pencandu NAPZA dan penyandang HIV/AIDS menjadi konselor adiksi dapat dipahami sebagai hasil sinergi antara agency individu dan struktur sosial.